2017
DOI: 10.1088/1742-6596/798/1/012116
|View full text |Cite
|
Sign up to set email alerts
|

Status of Experiment NEUTRINO-4 Search for Sterile Neutrino

Abstract: The experiment "Neutrino-4" started in 2014 on a model, then it was continued on a full-scale detector, and now, has provided the measurement result on dependence of the flux and spectrum of reactor antineutrinos on the distance of 6 -12 meters from the center of the reactor. One of the main problems is the correlated background from fast neutrons caused by space radiation. Attempts to suppress the background of fast neutrons by sectioning the detector have given some result. The relation of signal/background … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 31 publications
(57 reference statements)
0
14
0
Order By: Relevance
“…Before discussing our results, let us point out that the determination of the sensitivity to sterile neutrinos from oscillations is non-trivial from the statistical point of view. In particular, the results obtained under the assumption that Wilks' theorem [95] applies may differ from the ones obtained via Monte Carlo simulation [43,[96][97][98]. The sensitivity contours in this work have however been computed under the assumption that Wilks' theorem applies, in order to ease the comparison with previous literature.…”
Section: Sterile Neutrinosmentioning
confidence: 98%
“…Before discussing our results, let us point out that the determination of the sensitivity to sterile neutrinos from oscillations is non-trivial from the statistical point of view. In particular, the results obtained under the assumption that Wilks' theorem [95] applies may differ from the ones obtained via Monte Carlo simulation [43,[96][97][98]. The sensitivity contours in this work have however been computed under the assumption that Wilks' theorem applies, in order to ease the comparison with previous literature.…”
Section: Sterile Neutrinosmentioning
confidence: 98%
“…This is a range of oscillation lengths which can be explored in a model independent way in the new short-baseline reactor neutrino experiments (DANSS [98], Neutrino-4 [54], PROSPECT [99], SoLid [100], STEREO [101]) and in the SOX [102] and BEST [103] radioactive source experiments by measuring the reactor antineutrino rate as a function of distance. However, they will need to be sensitive to small oscillations with the amplitude 0.022 (0.0050) sin 2 2ϑ ee 0.19 (0.23) at 2σ (3σ).…”
Section: Global ν E Andν E Disappearancementioning
confidence: 99%
“…We do not consider the still preliminary data of the Neutrino-4 experiment[54] 3. We also correct, inTable 1, the misprints of the Rovno88 correlations in Tab.…”
mentioning
confidence: 97%
“…This and other anomalies found in neutrino oscillation experiments could be explained by a light sterile neutrino. Serebrov et al just reported on the first ever measurements with moving NEUTRINO-4 detector at the SM-3 reactor [61]. First results of the STEREO experiment at the ILL are expected for 2017 [62].…”
Section: Fundamental Neutron Physicsmentioning
confidence: 97%